Pharmacological elevation of anandamide impairs short-term memory by altering the neurophysiology in the hippocampus - Goonawardena, Anushka V (2011)
In rodents, many exogenous cannabinoid agonists including Δ(9)-THC and WIN 55,212-2 (WIN-2) have been shown to impair short-term memory (STM) by inhibition of hippocampal neuronal assemblies. However, the mechanisms by which endocannabinoids such as anandamide and 2-arachidonylglycerol (2-AG) modulate STM processes are not well understood. Here the effects of anandamide on performance of a Delayed Non-Match to Sample (DNMS) task (i.e., STM task) and concomitant hippocampal ensemble activity were assessed following administration of either URB597 (0.3, 3.0mg/kg), an inhibitor of the Fatty Acid Amide Hydrolase (FAAH), AM404 (1.5, 10.0mg/kg), a putative anandamide uptake/FAAH inhibitor, or R-methanandamide (3.0, 10.0mg/kg), a stable analogue of anandamide. Principal cells from hippocampal CA3/CA1 were recorded extracellularly by multi-electrode arrays in Long-Evans rats during DNMS task (1–30s delays) performance and tracked throughout drug administration and recovery. Both R-methanandamide and URB597 caused dose- and delay-dependent deficits in DNMS performance with suppression of hippocampal ensemble activity during the encoding (sample) phase. R-methanandamide induced effects were not reversed by capsaicine excluding a contribution of TRPV-1 receptors. AM404 produced subtle deficits at longer delay intervals but did not alter hippocampal neuronal activity during task-specific events. Collectively, these data indicate that endocannabinoid levels affect performance in a STM task and their pharmacological elevation beyond normal concentrations is detrimental also for the underlying physiological responses. They also highlight a specific window of memory processing, i.e. encoding, which is sensitive to cannabinoid modulation.